Kerapuhan pada kayu salib: Sebuah refleksi spiritualitas pelayanan terhadap kaum disabilitas di Gereja Toraja - Silaban, Tri Oktavia Hartati; Marrung, Roby; Masiku, Jefry L. (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
This article is backgrounded by concern for groups of people with disabilities who sometimes do not receive optimal services in the church. This situation makes them seem marginalized from other congregation members, while church services greatly influence the quality of the congregation's faith growth, including people with disabilities. This article aims to show the theological construction of spirituality serving people with disabilities through the narrative of fragility on the cross. The method used is interpretive descriptive analysis, based on a literature study regarding the narrative of the cross of Christ from various references and observations in several Toraja churches related to services for people with disabilities. The narrative of the cross shows that Christ's humanity was unable to escape suffering until death. The appreciation of the cross, which shows Christ's disability, is an expression of the fragility that He embraced in love so that through it, the spirituality of serving people with disabilities can be built and developed.AbstrakTulisan ini dilatarbelakangi oleh keprihatinan terhadap kelompok penyandang disabilitas yang kadangkala tidak mendapatkan pelayanan secara maksimal di gereja. Situasi tersebut membuat mereka seolah tersisihkan dari anggota jemaat yang lain, sementara pelayanan gereja sangat memengaruhi kualitas pertumbuhan iman jemaat, termasuk kaum disabilitas. Artikel ini bertujuan untuk menunjukkan konstruksi teologis tentang spiritualitas melayani kaum disabilitas melalui narasi kerapuhan pada kayu salib. Metode yang digunakan adalah analisis deskriptif interpretatif, berbasis pada kajian literatur tentang narasi salib Kristus dari beragam referensi dan observasi pada beberapa Geraja Toraja terkait pelayanan terhadap penyandang disabilitas. Narasi kayu salib memperlihatkan kemanusiaan Kristus tidak mampu melepaskan diri dari penderitaan hingga kematian. Penghayatan pada kayu salib yang memperlihatkan ketidakmampuan Kristus merupakan ekspresi kerapuhan yang direngkuh-Nya dalam cinta, sehingga melaluinya spiritualitas melayani kaum disabilitas dapat dibangun dan dikembangkan.